2015
DOI: 10.1007/s00404-015-3710-5
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary OBGYN morbidity and mortality conference

Abstract: M&M plays a crucial role not only in patient care, but also in resident education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…). The application of our selection criteria resulted in the inclusion of 67 studies, including eight surveys, four literature reviews, 33 case studies with no comparison or pre/post‐intervention evaluation, nine case studies with pre/post‐intervention evaluations, seven case studies with a comparison, one ethnography study, two qualitative observations and three opinion papers (Table ). Case studies took the form of descriptive programme reviews of an MMR model and related evaluations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…). The application of our selection criteria resulted in the inclusion of 67 studies, including eight surveys, four literature reviews, 33 case studies with no comparison or pre/post‐intervention evaluation, nine case studies with pre/post‐intervention evaluations, seven case studies with a comparison, one ethnography study, two qualitative observations and three opinion papers (Table ). Case studies took the form of descriptive programme reviews of an MMR model and related evaluations.…”
Section: Resultsmentioning
confidence: 99%
“…For patient safety, objectives ranged from tracking errors to training in QI methodology . Specific goals included tracking adverse events, analysing preventable errors, and translating findings to QI initiatives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Standardization of the review process and prospective, standardized data collection have been found to result in several benefits in human medicine, improving the accountability and quality of mortality data along with the identification of quality of care issues and supporting patient care quality improvement efforts, particularly for programs targeting the surgical patient . Standardizing the format of MMR has also been shown to improve residents' understanding of medical concepts presented in rounds . Such relationships are well established in human medicine; programs such as the American College of Surgeons (ACS) National Surgical Quality Improvement Programs (NSQIP) have been shown to capture more complications and quality issues when paired with MMR than either method alone.…”
Section: Discussionmentioning
confidence: 99%